Studies of Small Molecules Binding to Xanthine Oxidase Modeled After Urate Binding - Chang, Keng; Colwitz, Eric E.; Yang, Thao (My University, 2020)
We will present the binding results of 4-aminopyrazolo[3,4-d] pyrimidine and 4-amino-1H-pyrazolo[3,4-d] pyrimidine-6-ol binding to xanthine oxidase (XOD). XOD is an enzyme found in the human serum and lungs. The disease gout is caused by formation of high level of uric acid in the blood. Molecules that can bind to XOD are potential inhibitors, which could be developed as possible remedies for treating gout symptoms. The compounds consist of the pyrazolopyrimidine skeletal structure with different peripheral groups around the fused rings. The binding studies were first carried out by computer docking of the molecules onto the XOD active site, then the results of interactions between the docked molecule and side chain groups, as well as the affinity energies, were evaluated compared to the known binding of uric acid and allopurinol to XOD. The computer docking results showed that these molecules formed similar hydrogen bonding pattern and hydrophobic interactions at the active side when compared to the results obtained by docking uric acid and allopurinol. The binding of these molecules to XOD was also carried out in solution by the technique Saturation Transferred Difference NMR spectroscopy. The binding results obtained from the NMR experiments showed that both molecules have interactions with XOD.
Keywords: Protein Bonding